10-m Shuttle Ride Test in Youth With Osteogenesis Imperfecta Who Use Wheelchairs: Feasibility, Reproducibility, and Physiological Responses. Issue 5 (1st May 2016) - Bongers, Bart C.; Rijks, Ester B.G.; Harsevoort, Arjan G.J.; Takken, Tim; van Brussel, Marco
Abstract : Background: Physical fitness levels in youth with osteogenesis imperfecta (OI) who use wheelchairs are unknown. The 10-m Shuttle Ride Test (SRiT) has recently been introduced as a field test to determine cardiorespiratory fitness in children with cerebral palsy who self-propel a wheelchair. Objective: The purpose of this study was to investigate the feasibility and reproducibility of the SRiT, as well as the physiological responses to the SRiT, in youth with moderate-to-severe OI between 8 and 25 years of age who self-propel a wheelchair at least for long distances. Design: A test-retest design was used. Methods: Thirteen patients with OI (8 boys, 5 girls; mean±SD values for age=15.5±6.4 years) using a manual wheelchair performed 2 SRiTs within 2 weeks. Adverse events, reached stage, peak heart rate (HRpeak), peak respiratory exchange ratio (RERpeak), peak oxygen uptake (V̇o 2 peak), and peak minute ventilation (V̇e peak) were the main outcome parameters. Results and Discussion: All participants performed a maximal effort at both SRiTs (mean±SD values for HRpeak of 195±9 beats per minute [bpm], RERpeak of 1.32±0.16, V̇o 2 peak of 25.4±5.6 mL·kg −1 ·min −1, and V̇e peak of 47.9±18.6 L·min −1 ), without adverse events. The intraclass correlation coefficient of the reached stage showed excellent reliability (.95). Limits of agreement (LoA) analysis revealed acceptable LoA for reached stage (mean bias=−0.58, range=−2.50 to +1.35). There was a low correlation between reached stage and V̇o 2 peak ( r =.61 and r =.45 for the first and second SRiTs, respectively). Limitations: The influence of wheelchair properties and individually adjusted wheelchair designs was not examined. Conclusions: The SRiT appears to be a feasible, safe, and reproducible maximal field test in youth with OI using wheelchairs at least for long distances. This field test might be useful to provide an indication of physical fitness and to assess the efficacy of interventions on physical fitness in these patients.